ANALISIS PERBANDINGAN PENGUKURAN PENCIPTAAN NILAI PEMANGKU KEPENTINGAN: PENDEKATAN BOBOT ENTROPI DAN METODE PENJUMLAHAN - Sarita Vania Clarissa; Dewi Puji Rahayu (Faculty of Economics and Business, Universitas Warmadewa, 2026)
Stakeholder value creation has become an essential concept in evaluating corporate sustainability and performance. However, discrepancies remain in measuring stakeholder value, particularly between traditional aggregation methods and more advanced weighting techniques. This study aims to compare stakeholder value creation measurement using the entropy weighting method (Xu et al., 2023) and the summation approach (Signori et al., 2021). The study employs a quantitative approach with paired sample t-test analysis to examine the differences between the two measurement methods. The results show a significant difference (p-value < 0.05) between the two approaches, indicating that the entropy method provides a more accurate and consistent representation of stakeholder value distribution. The entropy method demonstrates lower standard deviation, reflecting better data homogeneity and precision. These findings suggest that entropy-based measurement is more appropriate for capturing stakeholder value creation compared to the traditional summation method.